한국 농업의 성장회계 분석: 1970-2010년 - 박춘성 (한국농촌경제연구원, 2012)
A growth accounting analysis of the Korean agricultural sector is carried out using time series data for the period 1970-2010. The results show that the average growth rate of Korean agricultural sector during the period is 2.24%, to which total factor productivity contributes 1.86%p and capital stocks contribute 2.13%p while labor and land contribute -1.41%p and -0.36%p respectively. Additional analyses show that sharp successive drops in the growth rate of agricultural GDP during the 1990s and 2000s are mainly attributed to sharp declines of total factor productivity during the same period. This implies that policies for encouraging agricultural growth should be targeted at raising incentives for investment in R&D and human capital formation, which help enhance agricultural productivity.
Keywords: 성장회계; 농업; 총요소생산성; growth accounting; agricultural sector; TFP